2019
DOI: 10.1016/j.celrep.2019.07.027
|View full text |Cite
|
Sign up to set email alerts
|

p63 and SOX2 Dictate Glucose Reliance and Metabolic Vulnerabilities in Squamous Cell Carcinomas

Abstract: Highlights d p63 and SOX2 drive elevated GLUT1 expression by SLC2A1 intronic enhancer transactivation d Enhanced GLUT1-mediated glucose influx fuels antioxidant production to promote survival d Systemic glucose restriction concurrently targets vital metabolic and oncogenic pathways d High random blood glucose is associated with poorer outcomes in squamous cancer patients

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
64
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(69 citation statements)
references
References 70 publications
3
64
1
1
Order By: Relevance
“…Moreover, the mechanisms driving polarization of mammary epithelial cells in vivo remain elusive and the connection between cell polarity and cell metabolism during mammary gland development, particularly during the high‐energy required stages like puberty and lactation, remains poorly understood. Notably, ∆Np63 regulates the expression of genes involved in metabolism in normal skin homeostasis and squamous cell carcinoma . As we have shown that ∆Np63 is critical for maintenance of tissue homeostasis of the mammary gland , it raises the intriguing possibility that ∆Np63‐dependent effects on high‐energy cellular metabolism during pubertal mammary gland development may contribute to this process.…”
mentioning
confidence: 95%
“…Moreover, the mechanisms driving polarization of mammary epithelial cells in vivo remain elusive and the connection between cell polarity and cell metabolism during mammary gland development, particularly during the high‐energy required stages like puberty and lactation, remains poorly understood. Notably, ∆Np63 regulates the expression of genes involved in metabolism in normal skin homeostasis and squamous cell carcinoma . As we have shown that ∆Np63 is critical for maintenance of tissue homeostasis of the mammary gland , it raises the intriguing possibility that ∆Np63‐dependent effects on high‐energy cellular metabolism during pubertal mammary gland development may contribute to this process.…”
mentioning
confidence: 95%
“…There is much interest, therefore, in the possibility of synergy with other drugs or other therapies. Hsieh, et al, for example, demonstrated that a squamous cell carcinoma that over expressed GLUT1 receptors showed attenuated growth when animals were on a KD [6]. There was, however, little regression of tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, this study indicates that p63 might act as a pioneer factor to establish open chromatin architecture to facilitate access by other lineage-survival factors, such as SOX2, to bind and activate target gene transcription during SCC development. Recently, it has been demonstrated that p63 cooperates with SOX2 to activate intronic enhancer cluster of GLUT1 (SLC2A1), which in turn facilitates GLUT1-mediated glucose influx and generation of NADPH and GSH in SCCs [ 28 ]. The p63 protein also binds to the enhancer region of ZNF185 and promotes its expression in keratinocyte during epithelial differentiation.…”
Section: Tp63 Establishes a Squamous Subtype-specific Enhancer Landscmentioning
confidence: 99%
“…ΔNp63α is the prominent isoform of the TP63 gene expressed in keratinocytes and basal cells of diverse epithelia [ 19 21 ] and various SCCs [ 2 ]. ΔNp63α promotes SCC development through regulating different target genes, including cell growth and proliferation [ 22 , 23 ], extracellular matrix (ECM)–receptor interaction [ 24 ], cell adhesion [ 25 27 ], glucose metabolism [ 28 , 29 ], anti-oxidant defense [ 30 , 31 ], DNA damage repair [ 32 , 33 ], terminal differentiation [ 34 , 35 ], and inflammation and angiogenesis [ 36 41 ] (Fig. 2 ).…”
Section: Introductionmentioning
confidence: 99%